DOES HAPPINESS IMPACT ACADEMIC ACHIEVEMENT? GLIMPSES FROM UNDERGRADUATE STUDENTS IN AFFILIATED COLLEGES OF BANGALORE CENTRAL UNIVERSITY - Avanesh, Neetha Mary; Devi N., Usha (International Journal of Psychosocial Rehabilitation, 2020)
The present study examines the impact of happiness on academic achievement of undergraduate students. To measure happiness, PANAS scale of positive and negative emotions was used. A sample of 282 students (140 males and 142 females) were drawn from various colleges, affiliated to Bangalore Central University, using convenient sampling technique and the data was collected through self-administered questionnaires. It was found that amongst the variables of happiness, all the positive emotion variables had a significant relationship with academic achievement whereas as only few negative emotions variables were significantly related to academic achievement. Further, only two variables viz., proud and inspiration had a positive and significant relationship with academic achievement in case of both female and male students, while three more variables viz., interest, strong and determination had a positive and significant relationship with academic achievement in case of male students. This difference may be due to the influence of other personal factors such as positive relationships with peers and teachers, relationship with family members, home environment, surroundings, parental support, study habits and good health.